THE INFLUENCE OF THE PERCEPTION OF USEFULNESS, PERCEIVED EASE OF USE, AND SATISFACTION OF THE MANDATORY TAX ON THE USE OF E-FILING FOR INDIVIDUAL TAXPAYERS - junawan, Junawan (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2019)
This research aims to determine how much influence perception of usefulness, perception of ease of use, and taxpayer satisfaction of the use of e-filling on employees of PT. Accentuates Medan. This research is associative research. The type of data used is the primary data obtained by distributing questionnaires to respondents on employees of PT. Accentuates Medan who has used e-filling of 50 respondents. Data collection techniques in this study are through questionnaires and observations. The author uses multiple linear analysis techniques with SPSS IBM software to process the data, first to test the data. The result of the research shows that the perception of usefulness has a positive and significant effect on the use of e-filling. Perceived ease of use has no positive and significant effect on the use of e-filling, and perception of user satisfaction has a positive and significant effect on the use of e-filling. However, perceptions of usability, perception of ease of use and user satisfaction simultaneously have a positive and significant influence on the use of e-filling.